Implementasi Nilai Nasionalisme Siswa Madrasah Ibtidaiyah dalam Penguatan Pendidikan Karakter Berbasis Budaya Sekolah - Dini, Sri Susanti Tjahja (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The purpose of the study was to determine the process of forming school culture, to determine the implementation model of national values ​​based on school culture in PPK and forms of evaluation based on school culture, and to monitor evaluation results at MIN 2 Kediri. This study used a qualitative approach, with subjects of the principal, vice principal, and teachers of MIN 2 Kediri. Data collection techniques include observation, direct or written interviews, and documentation studies. Data validity testing techniques using source and technology triangulation. The study results showed that school culture was built by involving all elements of the school. The implementation process was not done separately from or outside of learning through strengthening activities based on school culture. The positive effects of understanding national values ​​are increasing insight and positively impacting aspects of attitude and skills, which should also be seen at the evaluation stage.